2013
DOI: 10.1063/1.4824827
|View full text |Cite
|
Sign up to set email alerts
|

Wireless passive polymer-derived SiCN ceramic sensor with integrated resonator/antenna

Abstract: This paper presents a passive wireless polymer-derived silicon carbonitride (SiCN) ceramic sensor based on cavity radio frequency resonator together with integrated slot antenna. The effect of the cavity sensor dimensions on the Q-factor and resonant frequency is investigated by numerical simulation. A sensor with optimal dimensions is designed and fabricated. It is demonstrated that the sensor signal can be wirelessly detected at distances up to 20 mm. Given the high-temperature stability of the SiCN, the sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 25 publications
0
44
0
Order By: Relevance
“…Previous studies, which primarily focused on DC (direct current) behavior, revealed that the conductivity of PDCs could increase by several orders of magnitude with increasing pyrolysis temperature before crystallization [7,18,19]. The increase was believed to be caused by the sp 3 -sp 2 transition of the free-carbon phase [17], which was confirmed recently by Chen et al [20,21] and Wang et al [22] in different PDC systems. It was also demonstrated that PDCs exhibited a typical amorphous semiconducting behavior [23].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Previous studies, which primarily focused on DC (direct current) behavior, revealed that the conductivity of PDCs could increase by several orders of magnitude with increasing pyrolysis temperature before crystallization [7,18,19]. The increase was believed to be caused by the sp 3 -sp 2 transition of the free-carbon phase [17], which was confirmed recently by Chen et al [20,21] and Wang et al [22] in different PDC systems. It was also demonstrated that PDCs exhibited a typical amorphous semiconducting behavior [23].…”
Section: Introductionmentioning
confidence: 78%
“…However, AC conductive behavior has never been investigated in detail for polymer-derived ceramics. AC-response not only can reveal more structural information of heterogeneous systems such as PDCs studied here; but also will provide useful information for using the material for many applications, such as wireless sensors [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thickness and surface roughness of the metal film greatly influence the sensor signal strength [16]. Therefore, the screen-printing process should be smooth to reduce unnecessary loss.…”
Section: Design and Fabrication Of The Temperature Sensormentioning
confidence: 99%
“…Compared with traditional powder metallurgy‐based and polycrystalline ceramics, PDCs possess unique processing characteristics and structure . In addition, PDCs has demonstrated unique properties and potential applications at high temperatures . Especially, owing to their amorphous nature, the structure and properties of PDCs change significantly depending on the pyrolysis temperature.…”
Section: Introductionmentioning
confidence: 99%